Does economic stress matter for the rising divorce rate in China? A provincial perspective - Ul-Haq, Jabbar; Mushtaq, Shahzad; Visas, Hubert; Hye, Qazi Muhammad Adnan (Nurture, 2023)
Purpose: Marriage is an infinite bond between two partners that can be caused to fail by several factors. Economic stress leads to psychological stress and in some cases, marriage dissolution. The current study investigates the impact of economic stress (measured by the unemployment rate and inflation rate) on divorce rates using Chinese province-level panel data from 2010 to 2019. Design/Methodology/Approach: The panel fixed effects (FE) model, panel random effects (RE) model, and fixed effects- Driscoll and Kraay standard errors (DKSE) model were used for empirical analysis. Findings: The research findings support the hypothesized economic stress theory of divorce by Reuben Hill. According to the empirical findings, economic stress indicators such as unemployment and inflation have a positive and significant impact on the divorce rate in China and its regions. Furthermore, urbanization, education and mobile phone variables have a positive relationship with divorce rates except for children’s dependency. Contribution to literature: Taking into account both parties’ perspectives, this study contributes to the existing literature by looking at economic stress in the context of divorce. We are particularly interested in how economic stress affected the marriage relationship’s quality. We investigated the relationship between the unemployment rate, inflation rate and divorce rate in China’s 31 provinces for the period 2010-2019. The entire sample is then separated into three sub-samples: Eastern China, Central China and Western China.